Decompositions of $rg$-continuity via Idealization - K. Indirani; V. Rajendran; M. Meharin; O. Ravi (International Journal of Mathematics And its Applications, 2015)
In this paper, we introduce the notions of $rα g$-$\mathcal{I}$-open sets, $gpr$-$\mathcal{I}$-open sets, $C_r$-$\mathcal{I}$-sets and $C_r^*$-$\mathcal{I}$-sets in ideal topological spaces and investigate some of their properties and using these notions we obtain three decompositions of $r g$-continuity.